O vazio entre duas línguas em Sena & Sophia: centenários - Braz, Paulo (Texto Poético, 2021)
Resenha do livro: SANTOS, G.; RUAS, L.; CERDEIRA, T. C. (org.). Sena & Sophia: centenários. Rio de Janeiro: Bazar do Tempo, 2020.